Longitudinal Effects of Moderate to Vigorous Physical Activity in Physical Education Classes on Attention and Academic Achievement - Kyulee Shin; Sukkyung You; Mihye Kim (Behavioral Sciences)
Previous studies showed moderate to vigorous physical activity (MVPA) and aerobic fitness in adolescents are significant factors for cognitive and academic performance. Most previous studies have employed a cross-sectional design; consequently, the evidence on the longitudinal effect of physical education classes (PECs) on cognitive performance and academic achievement is limited. Therefore, the current study utilized a longitudinal design to examine the longstanding effect of MVPA during PECs on cognitive and academic performance across gender groups. Structural equation modeling analyses were employed to understand how MVPA influences youth academic achievement in a nationally representative sample (n = 2092). Study findings indicated that (a) MVPA exerted a direct effect on initial academic achievement as well as an indirect effect, which is mediated by middle school students’ attention in both gender groups; (b) MVPA had both long-term direct effects on academic achievement as well as indirect effects on attention, which ultimately affected the subsequent academic achievements of female middle school students.